Increasing Interest in Learning Natural and Social Sciences of Grade III Elementary School Students Through a Problem Based Learning Model Assisted by Interactive Media - Yulianti, Yulianti; Prasetyaningtyas, Rani; Widodo, Setyo Agung (Actual Insight, 2025)
Students' interest in learning Natural and Social Sciences (IPAS) subjects in elementary schools remains relatively low, as indicated by the limited active participation of students during lessons, which affects the achievement of optimal learning outcomes. This issue is mainly caused by the lack of varied learning models and media, resulting in monotonous and less engaging learning activities. This study aims to improve the learning interest of Grade III students at SDN Tanjungrejo 05 in the IPAS subject through the application of the Problem Based Learning (PBL) model assisted by Educaplay Froggy Jumps, a web-based educational game. The research employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles. Each cycle included four stages: planning, action implementation, observation, and reflection. Data were collected through observations of student activities and learning interest questionnaires administered before and after the actions. The collected data were analyzed using descriptive qualitative and quantitative techniques. The results indicated a significant increase in students' learning interest from the first to the second cycle. In the first cycle, the average learning interest reached 78%, increasing to 90% by the end of the second cycle. The use of the PBL model assisted by digital educational game media effectively enhanced students' attention, engagement, interest, and enjoyment in learning IPAS material. These findings suggest that integrating problem-based learning with interactive digital media can be an effective and enjoyable alternative strategy for increasing students' learning interest in elementary schools.